An LP Model for Optimizing a Supply Chain Management System for Steel Company - Alawneh, Ameen; Alrefaei, Mahmoud; Diabat, Ali; Al-Aomar, Raid; Faisal, Mohamed N (Lecture notes in engineering and computer science, 2014)
In this research, we have developed a linear programming formulation to describe Qatar steel manufacturing supply chain from suppliers to consumers. The purpose of the model is to provide answers regarding the optimal amount of raw materials to be requested from suppliers, the optimal amount of finished products to be delivered to each customer and the optimal inventory level of raw materials. The model is validated and solved using GAMS software. Sensitivity analysis on the proposed model is conducted in order to draw useful conclusions regarding the factors that play the most important role in the efficiency of the supply chain.